Perlindungan Hukum Terhadap Konsumen Jasa Titip Online Dari Cacat Barang - Lengkong, Lonna Yohanes; Situmeang, Tomson; Indraswari, Stefanie Hardiandra (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The personal shopper business is a new type of business in the trade industry that offers goods or services through social media using the internet networks. In running its business, the mechanism of the trust service profession is that a trust service acts as a third party that connects consumers with the main seller. This online entrustment service business products that are favored by consumers are usually in the form of fashion products, cosmetics, and accessories. However, this electronic transaction is vulnerable to defects in goods because they do not meet face-to-face. The formulation of the problem in this thesis is to examine the legal aspects of online delivery services from laws and regulations and legal protection for defects in goods to consumers. From this research it can be concluded that this online entrustment service in conducting a transaction is based on a sale and purchase agreement and authorization between the two parties in accordance with the Article 1320 of the Civil Code for the validity of an agreement, as well as online transactions based on the Electronic Information and Transaction Law. However, it is still based on a valid agreement requirement. If online entrusted service transactions occur defects in goods, then the laws and regulations in Indonesia, starting from the Civil Law, Consumer Protection Law, and Electronic Information and Transaction Law provide protection for consumers and business actors who are responsible for damage and hidden defects.